Examining Different Motor Learning Paradigms for Improving Balance Recovery Abilities Among Older Adults, Random vs. Block Training—Study Protocol of a Randomized Non-inferiority Controlled Trial - Nachmani, Hadas; Paran, Inbal; Salti, Moti; Shelef, Ilan; Melzer, Itshak (Frontiers in Human Neuroscience, 2021)
Introduction: Falls are the leading cause of fatal and nonfatal injuries among older adults. Studies showed that older adults can reduce the risk of falls after participation in an unexpected Perturbations Based Balance Training (PBBT), a relatively novel approach that challenged reactive balance control. This study aims to investigate the effect of the practice schedule (i.e., contextual interference) on reactive balance function and its transfer to proactive balance function (i.e., voluntary step execution Test, and Berg balance Test). Our primary hypothesis is that improvements in reactive balance control following block PBBT will be not inferior to the improvements following random PBBT. Methods and analysis: This double-blinded randomized controlled trial. Fifty community-dwelling older adults (over 70 years) will be recruited and randomly allocated to a random PBBT group (n=25) or a block PBBT group (n=25). The random PBBT group will receive 8 training sessions over 4 weeks that include unexpected machine-induced perturbations of balance during hand-free treadmill walking. The block PBBT group will be trained by the same perturbation treadmill system but only one direction will be trained in each training session and the direction of the external perturbations will be announced. Both PBBT groups (random PBBT and block PBBT) will receive a similar perturbation intensity during training (that will be customized to participant's abilities), the same training period, and the same concurrent cognitive tasks during training. The generalization and transfer of learning effects will be measure by assessing the reactive and proactive balance control during standing and walking before and after the 1-month of PBBT, for example, step and multiple steps and fall thresholds, Berg balance test, fear of falls, etc. The dependent variable will be rank transformed prior to conducting the ANCOVA to allow for non-parametric analysis. Discussion: This research will explore which of the balance re-training paradigms are more effective to improve balance reactive and proactive balance control in older adults (random PBBT vs. block PBBT) over 1-month. The research will address key issues concerning balance re-training: to older adults’ neuromotor capacities to optimize training responses and their applicability to real-life challenges.